A randomized controlled trial of parenteral glutamine in newborns receiving total parenteral nutrition (TPN) in Hospital Universiti Sains Malaysia (HUSM) - Mohamad Ikram, Ilias (2008)
Glutamine is a conditionally essential amino acid. Addition of glutamine in TPN of critically ill adults causes a reduction of complications such as infection. In neonates however, no clear benefits of addition of glutamine to TPN were shown in a limited number of studies, mainly performed in high income countries To determine whether the addition of glutamine to standard TPN in neonates in HUSM, Malaysia improves selected neonatal outcomes This was a double blinded randomized controlled trial. Babies admitted to the NICU during the 1-year study period, requiring TPN were eligible for inclusion. Subjects were randomized either to receive glutamine added TPN (intervention) or standard TPN (control). Primary outcome measures included time taken to reach full enteral nutrition, incidence of sepsis and NEC, time taken to achieve extubation, and time to discharge from NICU Out of 270 subjects included in the study 132 were randomized to the intervention group and 138 to the control group. There were no significant differences between the two groups in terms of baseline data. The median time taken to reach full enteral nutrition was similar for both intervention and control group (6 days in each group, p= 0.52). The time taken to achieve extubation was also similar in both groups (2 days in each group, p=O. 76). The incidence of necrotising enterocolitis in the intervention group was slightly lower than for the control group but the difference was not significant (5.8% vs. 7.1% , p=O. 68). The incidence of clinical sepsis and culture proven sepsis was also not significantly different in the intervention and the control group (15.7% vs10.2%,p=0.2J and 16.5% vs 15.7%, p=0.38 respectively). Sub-group analysis for preterm and term babies for the same outcomes also showed no statistically significant differences Addition of glutamine to TPN for neonates was not shown to improve outcome.